THE ABILITY OF PEDAGOGICAL CONTENT KNOWLEDGE (PCK) PROSPECTIVE ELEMENTARY SCHOOL TEACHERS (International Conference on Elementary Education, 2018)
This research is motivated that to support the professionalism of prospective elementary school teachers, it is necessary to be equipped with the right pedagogy and also the ability in mastering teaching materials, the collaboration between them is called Pedagogical Content Knowledge (PCK). This research aims to analyze the ability of PCK prospective of elementary school teachers when planning, implementing and reflecting learning. This research method uses a qualitative approach with descriptive design method. The three students sixth semester the involved as research subjects. Three participants were assigned to teach in class V about with water cycle material. Before implementing the lesson, each participant was asked to prepare the lesson plan, fill out the CoRe format and after carrying out the lessons asked to narrate the reflection on the implementation of the lesson in the PaP-eRs format. During the observations of execution of learning are conducted as complementary data. The research instrument used CoRe format, PaP-eRs format, RPP format and to plan instrument support that is observation sheet. The results showed that the ability of prospective teachers to plan the learning using CoRe is good enough because it is able to integrate pedagogical knowledge and content knowledge. But, it is still not been optimally implemented in making RPP. Prospective teachers have not yet fully formulated the objectives of learning, the selection of learning resources has not varied because it is only fixated on the student handbook, and in final activities do not tell about the present knowledge.